Application of graphene–polymer composite heaters in gas-assisted micro hot embossing. Issue 11 (18th January 2017) - Cheng, Cih; Ke, Kun-Cheng; Yang, Sen-Yeu
Abstract : This paper reports a novel hot embossing technique using rapid heating and uniform pressure for replication of microstructures on polymeric substrates. Abstract : This paper reports a novel hot embossing technique using rapid heating and uniform pressure for replication of microstructures on polymeric substrates. The rapid heating is made possible by a graphene–polymer composite heater that makes use of the exceptional thermal and electrical properties of graphene. The uniform embossing pressure is achieved by using gas as the pressing medium. A heating rate of 14 °C s −1 can be achieved by applying a voltage of 44 V to a heating area of 30 mm × 30 mm. A facility that integrates graphene-based heating and gas-assisted embossing is designed and implemented. Three microstructures, namely, microlens array, V-groove, and microcylinder array, are successfully replicated on three polymeric substrates. The accuracy and uniformity of replication over the area of 50 mm × 50 mm is also confirmed. Furthermore, the thermal cycle time is reduced to less than 30 s. This study proves the great potential of using graphene–polymer composite heaters in gas-assisted micro hot embossing for replication of microstructures for various applications.